Giant Cell Migration in Placentomes of Buffalo (Bubalus bubalis) - Ranjan, Rajesh; Singh, Opinder (Indian Journal of Veterinary Anatomy, 2013)
The present study was conducted on placentomes of 20 buffaloes ranging from 38 to 243 days of gestation to elucidate the role of migrating giant cells during the entire gestation period. Apart from the epithelium, giant cells were also found in between the cryptal walls and chorionic villi. The migration was first evident at 17 cm CVRL (105 days of gestation) with maximum migration at 31 cm CVRL (143 days). The migration disappeared during late gestation. The giant cells were strongly PAS-positive with some of the migrating cells having Alcianophilic granules. The cytoplasmic processes attaching the cryptal multinucleated cells with the trophoblastic epithelium were well evident at 20 cm CVRL (119 days) indicating the secretory properties of the giant cells.